Carbohydrate dependence during prolonged simulated cycling time trials - Torrens, S. L.; Areta, J. L.; Parr, E. B.; Hawley, J. A. (European Journal of Applied Physiology, 2016)
Purpose: We determined the effect of suppressing lipolysis via administration of Nicotinic acid (NA) and pre-exercise feeding on rates of whole-body substrate utilisation and cycling time trial (TT) performance. Methods: In a randomised, single-blind, crossover design, eight trained male cyclists/triathletes completed two series of TTs in which they performed a predetermined amount of work calculated to last ~60, 90 and 120 min. TTs were undertaken after a standardised breakfast (2 g kg-1 BM of carbohydrate (CHO)) and ingestion of capsules containing either NA or placebo (PL). Results: Plasma [free fatty acids] were suppressed with NA, but increased in the later stages of TT90 and TT120 with PL (p < 0.05). There was no treatment effect on time to complete TT60 (60.4 ± 4.1 vs. 59.3 ± 3.4 min) or TT90 (90.4 ± 9.1 vs. 89.5 ± 6.6 min) for NA and PL, respectively. However, TT120 was slower with NA (123.1 ± 5.7 vs. 120.1 ± 8.7 min, p < 0.001), which coincided with a decline in plasma [glucose] during the later stages of this ride (p < 0.05). For TTs of the same duration, the rates of whole-body CHO oxidation were unaffected by NA, but decreased with increasing TT time (p < 0.05). CHO was the predominant substrate for all TTs contributing between 83 and 94 % to total energy expenditure, although there was a small use of lipid-based fuels for all rides. Conclusion: (1) NA impaired cycling TT performance lasting 120 min, (2) cycling TTs lasting from 60 to 120 min are CHO dependent, and (3) there is an obligatory use of lipid-based fuels in TTs lasting 1-2 h.